Peran Terapi Reminiscence dengan Pendekatan Mendongeng Pada Lansia dengan Gangguan Kognitif di Desa Srigonco Kecamatan Bantur - Mizam Ari Kurniyanti; Ahmad Guntur A; Miftakhul Ulfa; Ari Dwi Sulaksono (Jurnal Ners, 2026)
Based on a quasi-experimental study in the village of Srigonco, this research concludes that reminiscence therapy using a storytelling approach is far more effective in improving cognitive function in older adults than puzzle therapy. The study, which involved 48 older adults with moderate cognitive impairment, showed that the storytelling group experienced a significant increase in MoCA-INA scores, from an average of 18.54 to 21.17, whilst the puzzle group only increased from 18.67 to 19.50. Through six intervention sessions themed around local culture and the history of independence, storytelling therapy proved capable of activating autobiographical and emotional memories in older adults more deeply than puzzles, which focus solely on general problem-solving stimulation. An independent t-test confirmed a significant difference in the final results of the two groups with a p-value of 0.001, affirming the superiority of this narrative-based therapy rooted in the past. Given its low cost, simplicity, and relevance to the cultural context of Indonesia, storytelling intervention is highly recommended for integration into elderly community health centre services to maintain their independence and quality of life.